GWAS meta-analysis of intrahepatic cholestasis of pregnancy implicates multiple hepatic genes and regulatory elements - Peter H. Dixon; Adam P. Levine; Inês Cebola; Melanie M. Y. Chan; Aliya S. Amin; Anshul Aich; Monika Mozere; Hannah Maude; Alice L. Mitchell; Jun Zhang; NIHR BioResource; Genomics England Research Consortium Collaborators; et al. (Nature Communications, 2022)
Investigation of variation in three cohorts has identified multiple genetic signals associated with the pregnancy-specific liver disorder, intrahepatic cholestasis of pregnancy, giving insight into the disease which can cause preterm birth and stillbirth.